9x^2 -c =d
add c to each side
9x^2 = c+d
divide by 9
x^2=(c+d)/9
take the square root on each side
x = +- sqrt ((c+d)/9)
simplify
x = +- 1/3 sqrt (c+d)
Answer: 1/3 sqrt (c+d), - 1/3 sqrt (c+d)
4/5
just take 16/20 and divde both be 4
Answer:
Step-by-step explanation:-16x^2 + 24x + 16 = 0.
A. Divide by 8:
-2x^2 + 3x + 2 = 0, A*C = -2*2 = -4 = -1 * 4. Sum = -1 + 4 = 3 = B, -2x^2 + (-x+4x) + 2 = 0,
(-2x^2-x) + (4x+2) = 0,
-x(2x+1) + 2(2x+1) = 0,
(2x+1)(-x+2) = 0, 2x+1 = 0, X = -1/2. -x+2 = 0, X = 2.
X-intercepts: (-1/2,0), (2,0).
B. Since the coefficient of x^2 is negative, the parabola opens downward. Therefore, the vertex is a maximum.
Locate the vertex: h = Xv = -B/2A = -24/-32 = 3/4, Plug 3/4 into the given Eq to find k(Yv). K = -16(3/4)^2 + 16(3/4) + 16 = 19. V(h,k) = V(3/4,19).
C. Choose 3 points above and below the vertex for graphing. Include the points calculated in part A which shows where the graph crosses the x-axis.
Answer:
x = 8
Step-by-step explanation:
40 + 6x + 2 = 90 {Complementary angles}
Combine like terms
40+ 2 + 6x = 90
42 +6x = 90 {Subtract 42 form both sides}
6x = 90 - 42
6x = 48 {divide both sides by 6}
6x/6 = 48/6
x = 8
Answer:
(i) (f - g)(x) = x² + 2·x + 1
(ii) (f + g)(x) = x² + 4·x + 3
(iii) (f·g)(x) = x³ + 4·x² + 5·x + 2
Step-by-step explanation:
The given functions are;
f(x) = x² + 3·x + 2
g(x) = x + 1
(i) (f - g)(x) = f(x) - g(x)
∴ (f - g)(x) = x² + 3·x + 2 - (x + 1) = x² + 3·x + 2 - x - 1 = x² + 2·x + 1
(f - g)(x) = x² + 2·x + 1
(ii) (f + g)(x) = f(x) + g(x)
∴ (f + g)(x) = x² + 3·x + 2 + (x + 1) = x² + 3·x + 2 + x + 1 = x² + 4·x + 3
(f + g)(x) = x² + 4·x + 3
(iii) (f·g)(x) = f(x) × g(x)
∴ (f·g)(x) = (x² + 3·x + 2) × (x + 1) = x³ + 3·x² + 2·x + x² + 3·x + 2 = x³ + 4·x² + 5·x + 2
(f·g)(x) = x³ + 4·x² + 5·x + 2